Multilayer dual-band bandpass filter / Eliz Azima Abdul Aziz - Abdul Aziz, Eliz Azima (2015)
This paper concentrates on designing a dual band bandpass filter suitable for wireless application. The filter is using multilayer technique by connecting two-quarter wavelength parallel coupled-lines to two half-wavelength lines through vias mode. The impact of the topology proposed, showing influence of the different impedance such as line impedance; Zr, even mode impedance; Zoc and odd-mode impedance; Zoo. Those parameters were analysed thoroughly. The filter was designed using TRF45 (Taconic) with reference frequency of 2 GHz by using multilayer technique. Observations on the controlling parameters arc conducted to investigate the effect of the transmission zeros.